DSC651: Data Representation and Reporting Techniques / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2018)
This course intends to introduce concepts and practices behind effective data representation and reporting techniques. The course explores current data representation that is analyzed for the content, methods and design strategies. The objective is to provide students with analytical tools that can benefit the design process of representing data and reporting information.